Concrete reinforcement using composite fiberglass-based materials - Benzerga Ahmed Lamine; Amieur Mohamed; Rabehi Rachid (The Journal of Engineering and Exact Sciences)
Numerous existing structures, both old and new, have serious load-bearing capacity issues, which, in some cases, could endanger the safety of their users. In fact, we can say that these structures are nearing (or have already reached) the end of their useful lives, necessitating the need to find technical and financial solutions to renovate them as efficiently as possible. Many reinforced concrete bridges experience advanced states of deterioration as a result of extended exposure to hostile environments or even continuously rising use loads. Additionally, since the time of their construction, the technical standards used for the design and dimensioning of the old structures have had to be updated. As a result, some structural components that are still in use do not adhere to the standards for response to loads. In fact, it is frequently less expensive to reinforce the structural components of buildings than to perform a full reconstruction, especially now that, thanks to technological advancements, a variety of reinforcement techniques are still available and their costs are decreasing. One such technique involves externally reinforcing reinforced concrete elements with composite materials because of their superior strength-to-weight ratio and resistance to abrasion. Additionally, these composite materials can be utilized for column containment as well as shear and bending reinforcement for beams. This study aims to evaluate the impact of glass fibers on the general behavior of concrete, in particular on its resistance, deformations, and ductility, using FRP: Fiber-reinforced plastics are materials generally formed of two main and distinct elements: the fiber, "made from glass," and the matrix, "an epoxy resin that allows the transfer of loads between the fibers. The results of the specimens' cyclic loading tests attest to the significance of the contribution that concrete specimen confinement with FRP can make in terms of deformation and resistance to compression after the completion of static loading tests. However, these tests on the specimens' ability to withstand loading and unloading cycles reveal a very significant improvement.